A Meta-Analysis of Ten Learning Techniques - Donoghue, Gregory M.; Hattie, John A. C. (Frontiers in Education, 2021)
This article outlines a meta-analysis of the 10 learning techniques identified in Dunlosky et al. (2013a), and is based on 242 studies, 1,619 effects, 130,867 participants with an overall mean of .56. The most effective techniques are distributed practice and practice testing and the least effective (but still with relatively high effects) are underlining and summarization. A major limitation was that the majority of studies in the meta-analysis were based on surface or factual outcomes, and there is caution needed when applying these findings to more deeper and relational outcomes. Other important moderators included the presence of feedback or not, near or far transfer, and the effects were much greater for lower than higher ability students. It is recommended that more attention be paid to when, under what conditions, and how to teach the optimal techniques.